Effects of D-methionine in mice with noise-induced hearing loss mice. Issue 8 (August 2019) - Wang, Yanru; Qu, Yan; Chen, Xuzhen; Zhang, Pu; Su, Dan; Wang, Li; Yang, Feifei; Yang, Jiangdong
Objective: To study the effects of D-methionine in a mouse model of noise-induced hearing loss (NIHL). Methods: We investigated changes in auditory function and microscopic cochlear structure in a mouse model of NIHL, and carried out 4-hydroxynonenal (4-HNE) immunostaining and terminal deoxynucleotidyl transferase dUTP nick-end labeling, and examined expression levels of connexins 26 and 30 by western blot. Results: The auditory brainstem response threshold was significantly increased by noise exposure. Noise exposure also damaged the inner and particularly the outer hair cells in the cochlear basement membrane, while histochemistry demonstrated only scattered loss of hair cells in the basement membrane in mice treated with D-methionine before or after noise exposure. D-methionine inhibited apoptosis in the cochlear basement membrane, stria vascularis, and spiral ligament. 4-HNE expression in the basement membrane, stria vascularis, and spiral collateral ligament was increased by noise exposure, but this increase was attenuated by D-methionine. Connexin 26 and connexin 30 expression levels were reduced by noise exposure, and this effect was similarly attenuated by D-methionine administered either before or after noise exposure. Conclusion: D-methionine administered before or after noise exposure could rescue NIHL by protecting cochlear morphology, inhibiting apoptosis, and maintaining connexin 26 and 30 expression.